Gut microbiome is associated with metabolic syndrome accompanied by elevated gamma-glutamyl transpeptidase in men - Sheng, Shifeng; Yan, Su; Chen, Jingfeng; Zhang, Yuheng; Wang, Youxiang; Qin, Qian; Li, Weikang; Li, Tiantian; Huang, Meng; Ding, Suying; Tang, Lin (Frontiers in Cellular and Infection Microbiology, 2022)
Abstract It is predicted that by 2035, metabolic syndrome (MS) will be found in nearly more than half of our adult population, seriously affecting the health of our body. MS is usually accompanied by the occurrence of abnormal liver enzymes, such as elevated glutamyl transpeptidase (GGT). Accumulating evidence suggests that the gut microbiota plays an important role in MS, however, the association between gut microbiota and MS with elevated GGT has not been studied comprehensively. Especially there are few reports about its role in the physical examination population of males with MS and elevated GGT. By using the whole-genome shotgun sequencing technology, we performed a study of gut microbiome genome-wide association in 66 participants with MS and high levels of GGT (case group) and 66 participants with only MS and normal GGT level (control group). We found that participants in case group have decreased number of gut microbial species compared to those in control group. The overall microbial composition between the two groups is of significant difference. The gut microbiota in case group is characterized by increased levels of “harmful bacteria” such as Megamonas hypermegale, funiformis and unclassified, Klebsiella pneumoniae and Fusobacterium mortiferum; decreases levels of “beneficial bacteria” such as Faecalibacterium prausnitzii, Eubacterium eligens, Bifidobacterium longum and pseudocatenulatum, Bacteroides dorei and Alistipes putredinis. Besides, the pathways of POLYAMSYN-PWY, ARG+POLYAMINE-SYN, PWY-6305 and GOLPDLCAT-PWY were also increased in case group, which may play a role on the elevation of GGT by producing amine, polyamine, putrescine, and endogenous alcohol. Taken together, there are apparent alterations in the structure and function of the gut microbiome in males with MS and abnormal GGT levels, and it is high time to discover specific gut microbiome as a potential therapeutic target to those population. In-depth study of relevant mechanisms may provide some new ideas for the treatment of MS with elevated GGT.